The Relationship of Vaccination with the Effectiveness of Covid-19 Control Policies in Indonesia - Junaedi, Dedi; Norman, Efrita; Arsyad, M. Rizal; Salistia, Faisal; Hadi, Sholikul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
This study aims to analyze the relationship between vaccination and the effectiveness of policies to overcome the Covid-19 pandemic in Indonesia. The quantitative analysis method with a dummy variable multiple regression approach was used to examine the vaccination times series data, cases, deaths and recoveries of Covid-19 patients for the period December 2020 – August 2021. The results show vaccination (especially dose 2) and the PPKM policy (Enforcement of Restrictions on Community Activities). have a significant impact on increasing cases, deaths and recoveries of Covid-19. Every 1,000 doses of vaccination has the potential to add 59 recovered patients, 46 new cases and 2 deaths. The impact on recovery is relatively higher than the impact on additional cases and deaths. A similar trend occurs when considering the impact of PPKM policies (micro, emergency and levels 1-4) on the increase in recovery, which is relatively higher than the similar impact on the rate of increase in cases and deaths. The impact on increasing cases and deaths can be said to be a risk that needs to be considered in future policy implementation.